2018
DOI: 10.1111/nph.15442
|View full text |Cite
|
Sign up to set email alerts
|

TRM4 is essential for cellulose deposition in Arabidopsis seed mucilage by maintaining cortical microtubule organization and interacting with CESA3

Abstract: Summary The differentiation of the seed coat epidermal ( SCE ) cells in Arabidopsis thaliana leads to the production of a large amount of pectin‐rich mucilage and a thick cellulosic secondary cell wall. The mechanisms by which cortical microtubules are involved in the formation of these pectinaceous and cellulosic cell walls are still largely unknown. Using a reverse genetic approach, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…Developmental defects have been observed in cases of cellulose synthesis, and deposition is affected in seeds, roots, embryos, and among many other tissues [16][17][18][19]. The CW matrix is formed by other glucans, such as Xyloglucan (XG), a hemicellulose.…”
Section: Plant Cell Wall Modifications Are Coordinated To Developmentmentioning
confidence: 99%
“…Developmental defects have been observed in cases of cellulose synthesis, and deposition is affected in seeds, roots, embryos, and among many other tissues [16][17][18][19]. The CW matrix is formed by other glucans, such as Xyloglucan (XG), a hemicellulose.…”
Section: Plant Cell Wall Modifications Are Coordinated To Developmentmentioning
confidence: 99%
“…Recent reviews sequentially reported 54 genes (Francoz et al, 2015) and 82 genes (Phan & Burton, 2018). Since then, 12 additional genes have been characterized (Fabrissin et al, 2019;Kunieda, Hara-Nishimura, Demura, & Haughn, 2019;Li et al, 2018;Shimada et al, 2018;Šola, Gilchrist, et al, 2019;Takenaka et al, 2018;van Wijk et al, 2018;Voiniciuc et al, 2018;Wang et al, 2019;Yang et al, 2019) bringing the list to 94 genes so far. They constitute the continuously growing MSC toolbox that participate to a proper seed mucilage production and release in A. thaliana (Francoz et al, 2015;Voiniciuc, Yang, Schmidt, Günl, & Usadel, 2015).…”
Section: Diversity Of Myxodiasporymentioning
confidence: 99%
“…Previous studies have identified at least 59 genes affecting seed coat cell differentiation and maturation when disrupted in A. thaliana (North et al, 2014; Rautengarten et al, 2014; Francoz et al, 2015; Voiniciuc et al, 2015a; Voiniciuc et al, 2015b; Griffiths et al, 2016; Ralet et al, 2016; Wardhan et al, 2016; Saez-Aguayo et al, 2017; Polko et al, 2018; Takenaka et al, 2018; Voiniciuc et al, 2018; Yu et al, 2018; Šola et al, 2019; Yang et al, 2019). These genes fall into roughly three functional categories: epidermal cell differentiation, mucilage synthesis and secretion, and secondary cell wall synthesis ( Supplemental Table 1 ).…”
Section: Introductionmentioning
confidence: 99%